2021
DOI: 10.54783/jin.v3i3.455
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Work From Home Terhadap Kinerja Karyawan Di Masa Pandemi Covid 19

Abstract: Working from home (WFH) has been implemented at PT. Sakti Mandiri Gifari Makassar in order to investigate the impact of WFH on employee performance and employee performance procedures during the influenza epidemic. The descriptive quantitative methodologies were used in this study, and a sample of 113 respondents from PT. Sakti Mandiri Gifari Makassar was selected using a random sampling methodology for the study. On the basis of the findings of the descriptive statistical test analysis, the data validity test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
(6 reference statements)
1
4
0
1
Order By: Relevance
“…This statement is by what was reported by Alimuddin (2021) that the WFH variable has a positive (0.345) and significant (0.000) effect on the performance of the employees of Bank BTN Cabang Makassar. This study is by what was reported by Sulastri (2021) that WFH has a high correlation with employee performance (t = 4.757) and has a high relationship with a statistically significant effect (p = 0.000). During the Covid-19 pandemic, WFH had a significant effect on the performance of employees at the Badan Penelitian and Pengembangan Kota Medan (Sormin et al, 2021).…”
Section: Influence Of Wfh To Performancesupporting
confidence: 85%
“…This statement is by what was reported by Alimuddin (2021) that the WFH variable has a positive (0.345) and significant (0.000) effect on the performance of the employees of Bank BTN Cabang Makassar. This study is by what was reported by Sulastri (2021) that WFH has a high correlation with employee performance (t = 4.757) and has a high relationship with a statistically significant effect (p = 0.000). During the Covid-19 pandemic, WFH had a significant effect on the performance of employees at the Badan Penelitian and Pengembangan Kota Medan (Sormin et al, 2021).…”
Section: Influence Of Wfh To Performancesupporting
confidence: 85%
“…The implementation of WFH will not reduce the performance but can actually improve it during the pandemic, as research results from Lilis Sulastri (2021) show that work from home has a direct and significant effect on employee motivation and performance, this shows that employees who apply WFH can produce high performance. Likewise, the results of her research Ibriati Kartika Alimuddin (2021) that the AI, IoT) as well as reliable and secure infrastructure with the aim of supporting the development of Indonesia, maintaining the authority of the central bank and welcoming digital civilization.…”
Section: Work From Homementioning
confidence: 99%
“…A pleasant, comfortable work environment for employees is one way for companies to improve the performance of employees, while a work environment that is not in accordance with the work needs of employees can eventually lead to boredom and fatigue, thereby reducing employee performance and not carrying out their duties effectively and efficiently. Study by Agusra et al [4], and Puspitawati and Atmaja [27] shows that compensation has a significant effect on performance, as well as research of Sulastri [35] shows that the work environment affects employee performance. Research conducted by Agusra et al [4], Puspitawati and Atmaja [27], and Sugiono et al [34] show that compensation and work environment have a significant effect on employee performance.…”
Section: Introductionmentioning
confidence: 97%
“…In addition, the work environment is one of the most important components in employees completing work. The work environment in question is everything that is around employees that can affect themselves in carrying out the tasks assigned (Ghazali et al [16], Lussianda et al [21], and Sulastri [35]). There are two kinds of work environment, namely the physical environment and the non-physical environment.…”
Section: Introductionmentioning
confidence: 99%